Penguatan Peran Orang Tua Remaja melalui Edukasi Pengasuhan Anak Pubertas dan Literasi Keuangan Keluarga - Westerini Lusdani; Winta Panimba; Rati Pundissing; Dwibin Kannapadang; Agustinus Mantong (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This Community Service Program (PkM) aims to strengthen the role of adolescent parents through education on parenting during puberty and family financial literacy in Lembang Tondon Langi’, Tondon District, North Toraja Regency. Through two training sessions led by Ibu Rio Rita Pakan and Ibu Westerini, the program focused on enhancing the knowledge and skills of parents in addressing the challenges of parenting adolescent children and managing household finances. The first session, which addressed parenting during puberty, provided parents with insights into the characteristics of adolescent development and effective communication strategies. The second session, which focused on family financial management, offered practical skills in budgeting, debt management, and saving for the future. The results of the program showed that parents in Lembang Tondon Langi’ felt more prepared and confident in applying a more open and adaptive approach to parenting, as well as becoming more prudent in managing household finances. The enhancement of skills in both areas is expected to create more harmonious families and greater financial stability. The sustainability of the program is recommended through the formation of ongoing discussion groups and the active involvement of community leaders. This program has contributed positively to family welfare and the empowerment of parents in rural areas